Mute: controversies between music and silences, resources for opening up dialogue in the exhibition process at the Musée du quai Branly (Cadernos de Sociomuseologia, 2024)
The refusal to have multiple perspectives on the same story in exhibition spaces is not something new, and continuing to perpetuate the lack of dialogue is a choice. We commonly identify in exhibitions and collections where the plural voices that the objects represent are placed on “mute” – a reference to the expression that characterizes the absence of sound in audiovisual equipment.These processes of silencing towards the communities of origin of museum objects, when taken to the level of sound, reinforce as much or even more the invisibilization of people related to the context in which the object was created. In this article, we propose to work on ethnographic collections of musical instruments, questioning how contemporary art has found ways to propose necessary discussions aligned with research committed to the representation of people and human rights.To this end, an example of work dedicated to criticism and decolonial dialogue based on sound will be analyzed, created by the artist Youmna Saba, La Réserve des non-dits [The Unspoken Reserve], on display at the Musée du quai Branly, in Paris, between November 5th, 2022 and February 18, 2024. Additionally, the resources that artistic proposals have found to propose diverse dialogues will be addressed in order to achieve a more inclusive museology.The objective of the article is to problematize an action that, through music, has questioned silence and brought alternative forms of representation to exhibition spaces.Keywords: Musicology; Museology; Silencing; Exhibition; Decolonial.